Perception of acute angles - Viliūnas, Vilius; Vaitkevičius, Henrikas; Švėgžda, Algimantas (Psichologija, 1999)
Experiments are reported which examine the judgement of the mean orientation of a single straight line (lest line) in presence of nearby lines of somewhat different orientations (induction line). It is shown, that perceived orientation of a segment of the test line is biased towards orientation of the induction line when the distance between the test and the induction line less than 0.1 deg. When this distance between 0.1–0.8 deg. a segment of the test line is biased from orientation of induction line and when this distance more 0.8 deg. the orientation of a segment of the test line remains unchanged.